Association of Vitamin D Level With Clinical Status in Inflammatory Bowel Disease: A 5‐Year Longitudinal Study. (May 2016) - Kabbani, Toufic A; Koutroubakis, Ioannis E; Schoen, Robert E; Ramos‐Rivers, Claudia; Shah, Nilesh; Swoger, Jason; Regueiro, Miguel; Barrie, Arthur; Schwartz, Marc; Hashash, Jana G; Baidoo, Leonard; Dunn, Michael A; et al.
Abstract : OBJECTIVES: Emerging data suggest that vitamin D has a significant role in inflammatory bowel disease (IBD). Prospective data evaluating the association of vitamin D serum status and disease course are lacking. We sought to determine the relationship between vitamin D status and clinical course of IBD over a multiyear time period. METHODS: IBD patients with up to 5‐year follow‐up from a longitudinal IBD natural history registry were included. Patients were categorized according to their mean serum 25‐OH vitamin D level. IBD clinical status was approximated with patterns of medication use, health‐care utilization, biochemical markers of inflammation (C‐reactive protein (CRP) and erythrocyte sedimentation rate (ESR)), pain and clinical disease activity scores, and health‐related quality of life. RESULTS: A total of 965 IBD patients (61.9% Crohn's disease, 38.1% ulcerative colitis) formed the study population (mean age 44 years, 52.3% female). Among them, 29.9% had low mean vitamin D levels. Over the 5‐year study period, subjects with low mean vitamin D required significantly more steroids, biologics, narcotics, computed tomography scans, emergency department visits, hospital admissions, and surgery compared with subjects with normal mean vitamin D levels ( P <0.05). Moreover, subjects with low vitamin D levels had worse pain, disease activity scores, and quality of life ( P <0.05). Finally, subjects who received vitamin D supplements had a significant reduction in their health‐care utilization. CONCLUSIONS: Low vitamin D levels are common in IBD patients and are associated with higher morbidity and disease severity, signifying the potential importance of vitamin D monitoring and treatment.